COMPARATIVE ANALYSIS OF CARIES DISEASE INDICATORS IN CHILDREN AND ADOLESCENTS WITH METABOLIC SYNDROME - O.V. Klitynska; M.M. Leshko (Український стоматологічний альманах, 2025)
Dental caries is a biofilm-mediated, sugar-induced, multifactorial, dynamic disease that results in phasic demineralization and remineralization of dental hard tissues. The balance between pathological and protective factors influences the onset and progression of caries, and it is disrupted in metabolic syndrome.